Quantification of Long Head of the Biceps Tendon Motion After Loop 'N' Tack Suprapectoral Biceps Tenodesis. Issue 7 (21st July 2017) - Kelly, Brian J.; Schimoler, Patrick J.; Kharlamov, Alexander; Miller, Mark Carl; Akhavan, Sam
Objectives: Lesions of the long head of the biceps are one of the most frequent causes of shoulder pain, and they can be successfully treated with biceps tenotomy or tenodesis. The advantage of a biceps tenodesis is avoiding the potential development of a cosmetic deformity ("Popeye sign") or cramping muscle pain that can remain after tenotomy. Proponents of a subpectoral tenodesis believe that "groove pain" may remain a problem after suprapectoral tenodesis due to persistent motion of the biceps tendon within the bicipital groove. The objective of this study was to evaluate the motion of the biceps tendon within the bicipital groove before and after a suprapectoral tenodesis performed using the Loop 'N' Tack technique. Our hypothesis was that there would be minimal to no motion of the biceps tendon within the bicipital groove after the tenodesis. Methods: Six fresh-frozen cadaveric arms were obtained and dissected to expose the long head of biceps tendon and the bicipital groove from the transverse humeral ligament to the pectoralis major insertion. The scapula and ulna were affixed with inclinometers to measure motion in multiple planes. The biceps tendon and bicipital groove were marked with fiducials, which were tracked by two cameras focused on this region. The shoulder and elbow were taken through a full range of motion including scapular abduction, forward flexion, extension, internal rotation, and external rotation and elbow flexion and extension with a supinated, neutral, or pronated forearm. The translation of the biceps tendon was quantified as a function of scapular or forearm motion in each plane. A suprapectoral biceps tenodesis was then performed using the Loop 'N' Tack technique. The scapula and forearm were taken through the same motions, and the translation of the biceps tendon was quantified. A paired t-test was performed for each motion to determine if maximum biceps tendon translation in the bicipital groove was a function of tendon condition (native vs post-tenodesis). Results: There was minimal translation of the biceps tendon during elbow flexion and extension, both before and after tenodesis. There was significant translation of the biceps tendon in all planes of scapular motion in the native state, and the largest amount of translation was 20.73mm +/- 8.21mm during shoulder flexion and extension (Table 1). The translation of the biceps tendon after tenodesis was significantly reduced in every plane of scapular motion compared to the native state (p = 0.01 or p < 0.01 in all planes of motion). The largest amount of translation in any plane after tenodesis was 1.57mm +/- 0.98mm, which occured during shoulder flexion and extension (Table 1). Conclusion: In the native state, the translation of the biceps tendon within the bicipital groove ranges from 5.14mm - 20.73mm with scapular motion. There is statistically significant reduction in translation of the biceps tendon in all planes of scapular motion after the Loop 'N' Tack tenodesis (Figure 1), with a maximum translation of only 1.57mm. These data suggest that motion of the biceps tendon within the bicipital groove is essentially eliminated and should not be a cause of persistent pain. The Loop 'N' Tack biceps tenodesis is a simple, all-arthroscopic technique for patients with proximal biceps pathology. It is a viable alternative to subpectoral tenodesis, essentially eliminating all motion of the biceps tendon within the bicipital groove, and it should not lead to persistent "groove pain". Table 1. Native Post-Tenodesis Results Average (mm) S.D. (mm) Average (mm) S.D. (mm) P-Value Elbow Flexion: Supination 1.85 1.66 0.56 0.37 0.15 Elbow Flexion: Neutral 1.73 1.43 0.83 0.64 0.30 Elbow Flexion: Pronation 3.03 1.55 0.72 0.24 0.01 Glenohumeral: Internal/External Rot. 9.37 1.70 1.32 0.78 <0.01 Glenohumeral: Flexion/Extension 20.73 8.21 1.57 0.98 <0.01 Glenohumeral: Full Flexion 10.32 2.60 0.75 0.47 <0.01 Glenohumeral: Abduction 5.14 2.67 1.26 1.17 0.01